Current imaging of the optic disk and retinal nerve fiber layer - Burk, Reinhard; Völcker, Hans Eberhard (Current opinion in ophthalmology, 1996)
The optic nerve head and the retinal nerve fiber layer (RNFL) are the sites of clinically detectable glaucomatous tissue damage. Photographic techniques are used to document the optic disk and the RNFL to monitor patients with suspected primary open-angle glaucoma or to follow-up patients already suffering from this disease. New techniques such as laser scanning tomography (LST), scanning laser polarimetry, and optical coherence tomography have been introduced to quantify structural alterations with the aim of early detection of optic nerve or RNFL damage prior to functional loss. These novel, additional diagnostic tools are currently being evaluated in clinical practice. While scanning laser polarimetry and optical coherence tomography are discussed elsewhere in this volume, articles on LST and conventional techniques are considered here. Imaging and computed data processing allow for three-dimensional in vivo measurements in the range of micrometers. With regard to the structure of the optic nerve head, this aspect in the evaluation of the optic disk can be based on quantitative topographic data. We expect “topometry” to become an important additional tool in the early diagnosis and follow-up of patients with glaucoma. However, computed parameter readings should always be evaluated in a clinical context. The goal is to improve, combine, and integrate all the different diagnostic approaches to improve patient care for the benefit of those suffering from glaucoma.
Gesehen am 04.07.2024